Excelence a genderové předsudky v praktikách a vnímání přírodních vědců ve vedoucích a rozhodovacích pozicích - Marcela Linková (Gender a Výzkum)
How to assess quality has become one of the central concerns for contemporary research, not least because of the proliferation of research assessment systems around the globe. Concomitant with this has been the growing attention to factors that compromise the credibility of assessment, especially gender, ethnic, racial and geopolitical bias. In this paper I analyse how lab leaders and research managers in the natural sciences specifically construct excellence and relatedly the demands of the research profession, and how gender bias plays out in these imaginaries. The material for the study comes primarily from two highly successful public research institutes of the Czech Academy of Sciences and specifically from individual and group interviews with lab leaders and research managers on topics of research governance, assessment, and quality. The focus is on the natural sciences because the discipline has driven the introduction of research assessment in the country as well as research and innovation reforms more broadly since the new millennium. Building on the distinction between the logic of choice and the logic of care developed by Annemarie Mol (2008), I explore the limits of individual choice for conceiving excellence and the gendered outcomes it produces.